Disturbed functional connectivity between anterior default mode and sensory processing regions is linked to peripheral inflammatory markers and psychopathology in schizophrenia - Mlynek, Emanuel; Tan, Xiaolin; Lammertz, Sarah Edith; Schaffrath, Sabrina; Gründer, Gerhard; Schneider, Frank; Frodl, Thomas; Mathiak, Klaus; Gaebler, Arnim Johannes (Schizophrenia bulletin, 2025)
Both elevated inflammatory markers and aberrant functional connectivity have been detected in patients with schizophrenia, but there is limited knowledge on the relationship between the two phenomena. Some positive symptoms may arise from external misattribution of self-generated actions mediated by decoupling of the default mode network (DMN) with sensory processing regions. Since the anterior DMN also exhibits bidirectional interaction with the immune system, we hypothesized its decoupling would be associated with elevated inflammatory markers as well as the burden of positive symptomatology.Resting-state functional magnetic resonance imaging, diffusion tensor imaging (DTI), clinical and laboratory data (serum concentrations of interleukin-6 and C-reactive protein) were collected within a neuroimaging trial on schizophrenia. Neuroimaging data were assessed applying seed-to-voxel and region-of-interest-to-region-of-interest functional connectivity analyses as well as DTI tractography. Associations between neuroimaging and laboratory as well as behavioral data were studied employing regression analyses.For both inflammatory markers, a consistent pattern of hypo-connectivity emerged between the anterior DMN and different brain regions involved in sensory processing and self-monitoring. The strongest association was detected for the connectivity between the anterior DMN and the right parietal operculum which was not explained by the structural integrity of the respective white matter tract. Finally, this functional connection was correlated both with the burden of positive and negative symptoms.Our findings reveal a mechanistically plausible neurobiological link between inflammation and psychopathology in schizophrenia.
Gesehen am 23.06.2025